STUDI PENGARUH PENCAMPURAN SAMPAH DOMESTIK, SEKAM PADI, DAN AMPAS TEBU DENGAN METODE MAC DONALD TERHADAP KEMATANGAN KOMPOS - Badrus Zaman; Endro Sutrisno (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
This research using the domestic organic garbage which is mixed by rice bran and cane pulp, with the variation of mixing pursuant to ratio C/N and moisture is, cane pulp : domestic organic garbage equal to 1:4, 2:7, rice bran : domestic organic garbage, 1:4, 2:7, and also the mixture cane pulp : domestic organic garbage : rice bran, 2:10:2, 1:7:1. Conduct attempted by aerobic and Mac Donald method. So that pursuant to the research can be taken conclusion that mixing lock  up  the  rice  bran  and  cane  pulp with the  domestic  organic  garbage  is  slow  down  the compost maturity so that unnecessary of cane pulp mixing and rice bran of at domestic organic garbage  composting,  compost  quality  of  result  of  mixing as  according  to  value  of  compost quality  at  SNI  19-7030-2004.  Composition  which  it faster  the compost  maturity  is  control  and composition which it has good ratio C/N from 6 variation is variation AS 27 which it consists of two cane pulp and seven domestic organic garbage.